Parliamentary Scrutiny of Legislation under the Human Rights Act 1998 - Lester, Anthony (Victoria University of Wellington Law Review, 2002)
The enactment of the Human Rights Act 1998 in the United Kingdom has widely affected many aspects of the operation of Government, including the traditional separation of judiciary, legislature, and executive. This paper examines the scope and process adopted for the scrutiny of legislation within the framework of the Human Rights Act 1998. The particular focus canvasses the first year's operation of the Joint Committee on Human Rights and its role as watchdog.